2017
DOI: 10.1002/ente.201600719
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Comparison of Large‐Scale Standalone, Centralized, and Distributed Thermochemical Biorefineries

Abstract: We present a comparison of three strategies for the introduction of new biorefineries: standalone and centralized drop‐in, which are placed within a cluster of chemical industries, and distributed drop‐in, which is connected to other plants by a pipeline. The aim was to quantify the efficiencies and the production ranges to support local transition to a circular economy based on biomass usage. The products considered are biomethane (standalone) and hydrogen/biomethane and sustainable town gas (centralized drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…Through these measures, the heat demand could be reduced by as much as 20% in a future commercial plant, thereby increasing the chemical efficiency of the gasifier to the same extent (for more details see ). In addition, by introducing an alternative external heat source, for example, direct heating by electricity, the energy content of the produced gas could be increased even further, up to about 120% compared to the chemically bound energy of the ingoing fuel .…”
Section: Description Of and Results From The Technical Demonstrationsmentioning
confidence: 99%
“…Through these measures, the heat demand could be reduced by as much as 20% in a future commercial plant, thereby increasing the chemical efficiency of the gasifier to the same extent (for more details see ). In addition, by introducing an alternative external heat source, for example, direct heating by electricity, the energy content of the produced gas could be increased even further, up to about 120% compared to the chemically bound energy of the ingoing fuel .…”
Section: Description Of and Results From The Technical Demonstrationsmentioning
confidence: 99%
“…The chemical efficiency of an ABP plant has previously been evaluated . Here, an efficiency of 70% based on the energy of the dry part of the delivered biomass is assumed.…”
Section: Reference Data and Scale Factorsmentioning
confidence: 99%
“…The methanation technology, which has been used in commercial plants that are based on fossil fuels, had to be scaled down significantly to match the DFB gasifier. An analysis of the performance of the process concluded that it is technically feasible to reach a biomass‐to‐biomethane efficiency of up to 70% based on the lower heating value (LHV) and dry ash‐free (DAF) fuel …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A side‐effect of the operation of a DFB system is the transport of oxygen between the two reactors via oxidation/reduction of the bed material itself (for example, see Hallberg et al). The transported oxygen will cause partial oxidation of the produced gas, increasing the amount of CO 2 in the raw gas, which must later be separated, usually via an energy‐intensive amine process (see Alamia et al).…”
Section: Experimental Backgroundmentioning
confidence: 99%